Long-term survival with nivolumab followed by irinotecan after total gastrectomy in alpha-fetoprotein-producing gastric cancer: a case report and review of the literature - Takayo Ota; Katsuya Sakashita; Ryugo Sawada; Kurumi Seki; Hiroyuki Maeda; Noriko Tanaka; Toshimasa Tsujinaka (Surgical Case Reports, 2023)
Abstract Background Alpha-fetoprotein-producing gastric cancer (AFPGC) is a rare type of aggressive gastric cancer (GC) with a dismal prognosis. We present a patient with AFPGC who achieved long-term survival through a multidisciplinary approach. Case presentation A 67-year-old man with advanced GC was referred to our hospital for systemic chemotherapy. He was diagnosed with cStage IVB AFPGC. During 2nd-line treatment, we could not control bleeding from the GC itself. After complete resection, during chemotherapy, portal venous tumor thrombi (PVTTs) and liver metastases were identified. With nivolumab followed by irinotecan, the PVTTs and liver metastases disappeared. Without immunotherapy and chemotherapy for 23 months, the patient has survived for 48 months so far with no recurrence of GC. Conclusion Long-term survival with AFPGC can be accomplished by using several different approaches, such as surgery, immunotherapy, and chemotherapy.